Potential induced degradation in c-Si glass-glass modules after extended damp heat stress. (April 2023) - Mahmood, Farrukh ibne; Kumar, Akash; Afridi, Muhammad; TamizhMani, Govindasamy
Highlights: PID influence in fresh and DH-stressed commercial c-Si glass-glass bifacial modules is studied. It is better to study PID in DH-stressed modules instead of fresh ones as it is more field-representative due to reduced interfacial strengths in field-aged modules. Fresh modules undergoing PID show very low degradation, whereas modules that undergo PID after DH degrade by 11 to 12% in Pmax. The more degradation is due to lower interfacial adhesion bonds in DH-stressed modules. Most studies are either focused on one-cell modules or fresh samples for PID testing, which is not field representative. This study uses commercial modules for PID after DH stress to better understand the PID mechanisms. Since GG modules are expected to dominate the PV market in the future, understanding their failure modes is essential. Abstract: Traditional Glass-Backsheet (GB) photovoltaic (PV) modules have been the industry standard for a long time, but the Glass-Glass (GG) modules are quickly rising in popularity. PV modules installed in hot-humid climates with high string voltages can undergo potential induced degradation (PID). So far, to the best of our knowledge, only fresh modules with strong interfacial adhesion have been investigated for PID. However, in reality, the PV modules have weak interfacial adhesion after a few years of field exposure. Therefore, it is essential to evaluate PV modules with weakened interfaces. In this study, we investigated the PID susceptibility of PV modules with weakened interfaces after subjecting them to 2000 h of damp heat (DH2000) at 85 °C/85% relative humidity (RH) in an accelerated environmental chamber. Fresh GG modules were also stressed for PID to compare with PID degradation of DH-stressed modules. Pre- and post-characterization tests were done before, between, and after each stress method to determine the changes in electrical performance, cell metallization properties, and hotspot properties. It is observed that fresh GG modules showed little/no degradation (less than 1%) in maximum power (Pmax), whereas the GG modules that underwent sequential DH and PID degraded by 11% to 12%. Potential mechanisms for these degradations are also presented. The results presented in this study are critical for the industry, considering that the bifacial modules with GG construction will be dominant in the next 10 years.